HERBAL PHARMACEUTICALS AND CONTEMPORARY DEVELOPMENTS IN INNOVATIVE DRUG DELIVERY SYSTEMS - Aysha Aslam; Hammad Afzal; Rabia Munir; Hafsah Maryam; Muhammad Hammad Rasheed Baig; Isra Rasheed Baig; Sana Naseer; Kalim Ullah; Maria Siddique (International Journal of Pharmacy & Integrated Health Sciences)
Background: A novel drug delivery system represents an innovative method for administering pharmaceuticals that overcomes the constraints of conventional drug delivery systems. Objectives: This article provides an overview of diverse drug delivery strategies applicable to herbal applications and several examples. Methodology: The data was searched using different databases, including Google Scholar, Scopus, Web of Science and Pub Med. Results: The application of innovative drug delivery technology in herbal medicine may enhance efficacy and diminish the adverse effects of various herbal components and herbs. This encapsulates the fundamental concept of integrating innovative drug-delivery techniques within natural remedies. Therefore, it is essential to incorporate innovative drug delivery systems to address more severe disorders. People have used plants for food and medicine since ancient times, and they are considered natural remedies. Global efforts are to extract plant-based medicines from flora and bring them to market. Due to processing, standardization, extraction, and identification challenges, herbal medicines could not draw scientists' attention. However, due to technological advancements, novel drug delivery systems (NDDS) are developing revolutionary herbal medication delivery methods. Conclusion: There is great potential for monitoring drug delivery systems such as nanoparticles, niosomes, ethosomes, vesicles, micellar solutions, liquid crystal dispersions, hydrogels, and liposomes composed of minuscule components with sizes ranging from 10-400 nm. The main goals of creating such delivery methods are to minimize drug degradation, maximize bioavailability, enhance drug stability, reduce drug toxicity, and prevent undesirable side effects with the provision of drugs at the targeted site. Targeting refers to the capability to focus drug-loaded strategies at a desired time to perform their physiological function.